LOW HAEMOGLOBIN LEVEL AS POSITIVE PREDICTOR FOR FUNCTIONAL MATURATION OF NATIVE ARTERIOVENOUS FISTULA. - Muhammad Jamil; Rashid Usman; Muhammad Saeed (Journal of University Medical & Dental College, 2017)
ABSTRACT:OBJECTIVES: To assess the impact of low haemoglobin (Hb) concentration on maturation of arteriovenous ﬁstula (AVF).MATERIALS AND METHODS: This is a prospective observational study conducted in the Department of Vascular Surgery Combined Military Hospital Peshawar and Lahore from January 2015 to March 2016. A total of 96 patients fulﬁlling the inclusion criteria were included in the study. Based on their Hb levels, patients were divided into two groups; group A with Hb less than 8 g/dL (n=50) and group B with Hb more than 8 g/dL (n=46). All patients were assessed for maturation of AVF as per Kidney Disease Outcome Quality Initiative (KDOQI) guidelines.RESULTS: In group A, 92% (n=46) AVFs became functionally mature, whereas maturation rate in group B was 67.3% (n=31), with a P value of 0.004 between the two groups. CONCLUSION: Low level of Hb has statistically signiﬁcant positive impact on functional maturation of AVF.RUNNING TITLE: Low Hemoglobin as predictor for ﬁstula maturation